Daughters of the occupation : a novel of WWII - Sanders, Shelly, 1964- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2022)
Thirty years after a Jewish widow and her children are kept safe by their loyal housekeeper after the Nazis take over Latvia in 1940, she begs her estranged granddaughter to find out what happened to her son.
Includes: P.S. insights, interviews and more....author's note, further reading, and book club questions.
Keywords: Jews -- Fiction; World War, 1939-1945.; Rumbula Massacre, Rumbula, Latvia, 1941 -- Fiction; Grandparent and child -- Fiction; Family secrets -- Fiction; Rīga (Latvia) -- Fiction; Rumbula (Latvia) -- Fiction; Historical fiction